Both exhaled nitric oxide and blood eosinophil count were associated with mild allergic asthma only in non‐smokers. Issue 4 (April 2016) - Giovannelli, J.; Chérot‐Kornobis, N.; Hulo, S.; Ciuchete, A.; Clément, G.; Amouyel, P.; Matran, R.; Dauchet, L.
Summary: Background: The fractional exhaled nitric oxide (FENO) and the blood eosinophil count (B‐eos) are markers of eosinophilic inflammation used in the diagnosis and management of asthma. The relationships between smoking cigarette and both FENO and B‐eos are complex and raise questions about the association between these markers and asthma in smokers. Objective: To determine the relationships between both FENO and B‐eos on one hand and asthma and atopy on the other, according to smoking status. Methods: FENO and B‐eos were measured in, respectively, 1579 and 1496 of the 1607 middle‐aged adults randomly selected from the general population in the cross‐sectional ELISABET survey. Allergic asthma was defined as asthma (a self‐report of physician‐diagnosed asthma, and wheezing in the previous 12 months or the use of asthma medications) with atopy (allergic rhinitis or hayfever in the previous 12 months, or a previous positive prick test or allergen desensitization therapy). Non‐allergic asthma was defined as asthma without atopy. Results: The analysis included 812 (51.4%) never, 473 (30%) former and 294 (18.6%) current smokers. A total of 490 (32%) participants were atopic, 80 (5.1%) had allergic asthma, and 31 (2%) had non‐allergic asthma. Only 16.2% (18/111) of asthmatics were treated with glucocorticoid inhalants, suggesting that among them a majority of participants had mild asthma. A positive interaction between smoking status and allergic asthma was observed in multivariate models explaining FENO ( P  = 0.003) and B‐eos ( P  = 0.001). Thus, compared to those without allergic asthma, participants with allergic asthma had higher FENO values (+ 63.4%, 95% CI = [39; 92]) and higher B‐eos (+ 63.2% [38.2; 92.7]) in never and former smokers, but not in current smokers. Lastly, an analysis of receiver‐operating characteristic curves showed that each of the two markers was able to discriminate moderately allergic asthma but only in non‐smokers. Conclusions & Clinical Relevance: FENO and B‐eos were associated with the presence of mild allergic asthma only in non‐smokers, not in current smokers. These findings raise questions about the clinical value of FENO and B‐eos in smokers.